A survey of the library facilities and collections of the public elementary schools in Marikina City based on the standards for Philippine libraries a follow-up study - Hizon, Patricia Felise P.; Santos, Yhna Therese P. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2016)
This study focuses on the compliance of the public elementary school libraries in Marikina City with the collection and facility standards of the Standards for Philippine Libraries by the Department of Education.
This research is a follow-up on the study conducted by Torres in 1998 on the public elementary school libraries in Marikina City and their compliance to the standards set by the Department of Education, Culture and Sports. This study sought to determine (1) if the recommendations given by Torres in her study were implemented in the libraries; (2) the changes that occured to the libraries' collection and facilities after Torres' study; and (3) the difference on the compliance of the libraries to the standards back in 1998 and 17 years after.
Seventeen respondents were asked to participate in the survey; eight respondents were from the District I, and nine respondents from the District II of Marikina City. The questionnaire contains the following information needed: (1) profile of the respondent; (2) school profile; (3) library profile; (4) library personnel/staff; (5) physical facilities; (6) collection; (7) selection and organization; (8) preservation and security; and (9) planning for the library.
An interview with the respondents was also conducted to obtain further information and also their insights.
The public elementary school libraries in Marikina City were not able to comply with the standards set by the Department of Education. The libraries' collection, facilities and equipments did not meet the 2011 Standards for Philippine Libraries. Some of the recommendations by Torres were implemented in the libraries, but there were no changes to the libraries' collections and facilities.
The libraries rely on donations and there is not library staff with any library educational background in all the public elementary school libraries in Marikina City. Most of the library staff was not aware that a standard by the Department of Education should be implemented in their libraries and those who were aware does not apply it to their library. The libraries conduct library management by following the rules and regulations that they have come up with on their own, instead of following the 2011 Standards for Philippine Libraries. Improvements in the library service will be done if the libraries hire full-time licensed librarians, and the school administrations should also give greater importance and priority to their library.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Elementary school libraries -- Philippines -- Marikina City; Collection management (Libraries) -- Philippines -- Marikina City; School libraries -- Philippines -- Standards